2016
DOI: 10.1039/c6py01195k
|View full text |Cite
|
Sign up to set email alerts
|

The next step in precipitation polymerization of N-isopropylacrylamide: particle number density control by monochain globule surface charge modulation

Abstract: Many applications of poly(N-isopropylacrylamide) microgels necessitate robust control over particle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
2
36
0
2
Order By: Relevance
“…The power law exponent with respect to NIPAM concentration, determined here as 1.54 ± 0.07, is higher than expected based on the earlier results of 0.94 ± 0.08 36 and 1.05 ± 0.08. 35 However, given the limited amount of experimental data, the value is in reasonable agreement with previous work. As expected for radical solution polymerization, the power law exponent of 0.42 ± 0.03 in respect to APS concentration is close to half an order of magnitude lower than for the NIPAM concentration.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The power law exponent with respect to NIPAM concentration, determined here as 1.54 ± 0.07, is higher than expected based on the earlier results of 0.94 ± 0.08 36 and 1.05 ± 0.08. 35 However, given the limited amount of experimental data, the value is in reasonable agreement with previous work. As expected for radical solution polymerization, the power law exponent of 0.42 ± 0.03 in respect to APS concentration is close to half an order of magnitude lower than for the NIPAM concentration.…”
Section: Resultssupporting
confidence: 91%
“…Earlier studies have shown the polymerization rate to be close to the power law behavior of radical solution polymerization with R p ∝ [monomer][initiator] 1/2 shortly after initiation. 35,36 This is not surprising, given the abundant solubility of NIPAM in water, which implies that significant conversion takes place in the water phase during early reaction stages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations